Penilaian Tutor terhadap Penguasaan Pengelolaan Proses Pembelajaran - Andi Suci Anita (Jurnal Pendidikan Kewarganegaraan, 2017)
System Remote applied the Open University (UT) in learning, requires students to study independently at their own initiative in studying the teaching materials provided by UT, tasks, strengthen skills, and apply the experience in the field or the work they can do individually or groups. The Open University in addition to providing assistance through tutorials Online learning, also facilitate learning through tutorial assistance Face to Face. Tutorial serves as a driver at the same time trigger the process of student learning so that students have the will and the ability to observe, think, behave and act in the face of a concept of science and technology as the result of a learning process. Tutorial process guided by a tutor who acts as a facilitator and motivator in the tutorial. Tutor greatly affect the performance has yet tutorial. For it to investigate the performance of tutors UPBJJ-UT Banjarmasin through student assessment D2 Library. Assessment is done through kuiseioner which are distributed in 4 pokjar namely Tapin District, Upper South River, Upper North River and Tabalong. Based on the survey results revealed that the performance tutor UPBJJ-UT Banjarmasin on mastery learning management an average score of 3.10 Good category. Keywords : tutor performance, face to face tutorial, UPBJJ-UT Banjarmasin